2009
DOI: 10.4049/jimmunol.0803574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Cathepsin G As a Functional Target of Boswellic Acids from the Anti-Inflammatory Remedy Frankincense

Abstract: Frankincense preparations, used in folk medicine to cure inflammatory diseases, showed anti-inflammatory effectiveness in animal models and clinical trials. Boswellic acids (BAs) constitute major pharmacological principles of frankincense, but their targets and the underlying molecular modes of action are still unclear. Using a BA-affinity Sepharose matrix, a 26-kDa protein was selectively precipitated from human neutrophils and identified as the lysosomal protease cathepsin G (catG) by mass spectrometry (MALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 44 publications
0
83
0
Order By: Relevance
“…Pull-down assays using immobilized BAs were previously applied to demonstrate a direct interference of BAs with COX-1, 12S-LOX and cathepsin G (Poeckel et al, 2006b;Siemoneit et al, 2008;Tausch et al, 2009), supporting the suitability of this methodology for target identification. The SPR-based ligand-analyte studies revealed KD values of 5.2-23 mM for 3-Ooxaloyl-KBA, and these values fit the IC50 (5 mM) of 3-O-oxaloyl-KBA in the mPGES1 cell-free assay, suggesting specific binding to mPGES1 and hence a direct relation between enzyme binding and interference with mPGES1 activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pull-down assays using immobilized BAs were previously applied to demonstrate a direct interference of BAs with COX-1, 12S-LOX and cathepsin G (Poeckel et al, 2006b;Siemoneit et al, 2008;Tausch et al, 2009), supporting the suitability of this methodology for target identification. The SPR-based ligand-analyte studies revealed KD values of 5.2-23 mM for 3-Ooxaloyl-KBA, and these values fit the IC50 (5 mM) of 3-O-oxaloyl-KBA in the mPGES1 cell-free assay, suggesting specific binding to mPGES1 and hence a direct relation between enzyme binding and interference with mPGES1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that impaired PGE2 biosynthesis is the result of the selective inhibition of the transformation of PGH2 to PGE2 by interference of BAs with mPGES1, rather than with COX-2 or other distal events (such as AA release). In particular b-BA, the major BA present in frankincense that reaches the highest plasma levels (up to 10.1 mM) among the BAs in treated humans (Buchele and Simmet, 2003;Tausch et al, 2009), suppressed PGE2 formation in human whole blood, again without significant reduction of 6-keto PGF1a or TXB2 levels. Interference with COX-1 was excluded as 12-HHT formation in whole blood was unaffected by b-BA, although BAs (in particular AKBA and KBA) may inhibit COX-1 in cell-free and cell-based models at higher concentrations .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations